36.2k views
17 votes
Solve the system of equations (1 point)
y = 2x(squared) – 3
y = 3x - 1

User Jimmt
by
5.5k points

1 Answer

5 votes


\huge\fcolorbox{blue}{aqua}{Answer:}

════════════════════

1.


y = {2x}^(2) - 3


{2x}^(2) - 3 = y


{2x}^(2) = y + 3


\frac{2x^(2)} {2} = (y + 3)/(2)


{x}^(2) = (y + 3)/(2)


x = \sqrt (2y + 6)/(2)

───────────────────

2.


y = 3x - 1


3x - 1 = y


3x = y + 1


(3x)/(3) = (y+1)/(3)


x = (y + 1)/(3)

═══════════════════

Step-by-step explanation:

#Carry on learning

User Seganku
by
5.4k points